2013
DOI: 10.2980/20-1-3559
|View full text |Cite
|
Sign up to set email alerts
|

A year in an ant's life: Opportunism and seasonal variation in the foraging ecology ofAphaenogaster senilis

Abstract: Ants are important consumers in most terrestrial ecosystems. They show a great diversity of diets and foraging strategies. Here, we analyzed how circannual variation in resource use by the Mediterranean species Aphaenogaster senilis is related to colony life cycle and resource availability. In southwestern Spain, this species is active almost yearround, but foraging intensity decreases 10fold between March and November, following larval production. In the summer, ants refrain from foraging at midday to avoid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
0
14
0
1
Order By: Relevance
“…However, they did observe that different plant items were collected depending on their availability. Indeed, the complementary use of traditional observations and isotopic dietary analysis in ants has confirmed that nitrogen isotopic values shift when there is a small modification in the diet (Caut et al 2013a). In our study, fire had no effect on overall ant isotopic values across time; no difference was observed between values obtained 1 month and 1 year after fire.…”
Section: Fire's Effects On a Gibbosa Sex Allocationmentioning
confidence: 98%
See 1 more Smart Citation
“…However, they did observe that different plant items were collected depending on their availability. Indeed, the complementary use of traditional observations and isotopic dietary analysis in ants has confirmed that nitrogen isotopic values shift when there is a small modification in the diet (Caut et al 2013a). In our study, fire had no effect on overall ant isotopic values across time; no difference was observed between values obtained 1 month and 1 year after fire.…”
Section: Fire's Effects On a Gibbosa Sex Allocationmentioning
confidence: 98%
“…In addition, food may be unevenly distributed among colony members (queens, workers, larvae [LI], etc.). Thus, stable isotope analysis provides a powerful alternative approach in such circumstances (Kelly 2000;Caut et al 2009Caut et al , 2013a. This method is based on the notion that an organism's nitrogen and carbon isotopic ratios (d 13 C and d 15 N) provide a record of the resources it has assimilated (see Post 2002;for review).…”
Section: Introductionmentioning
confidence: 99%
“…Primary dispersal allowed transporting most A. italicum fruits an average of 2-4 m away from the mother plant. This corresponds to the average foraging distance of A. senilis (Cerdá et al, 2009). This dispersal distance may be sufficient to promote the colonization of new habitats for small herbs like A. italicum but might not be relevant for shrubs whose fruits can be transported a 100 m by birds (Traveset, 1994;Hulme, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…had a quick response on day on the first day that disappeared on the second day. Aphaenogaster senilis Mayr is an opportunistic species that is able to adjust its diet according to the resources of the area (Caut et al, ). This characteristic may help exploit dynamic resources and may explain the higher number of captures in the first few hours after setting the traps when environmental disturbances are most fresh.…”
Section: Discussionmentioning
confidence: 99%